Satu analisis ringkas konsep dan teori sastera Islam di Malaysia - Yaacob, Adli (Fakulti Pengajian Islam, Universiti Kebangsaan Malaysia, 2007)
This article revolves around the polemics and critics of Islamic Literature in Malaysia. It emphasizes on the meaning of literature and its relation to Islam. It also highlights the role of Islam in nurturing literature and culture.Islamic literature polemics has become a hot topic for sometime among Malaysian literary men,looking for the meaning of 'Islamic literature' and 'Islamic literary theory'.This paper among others tries to analyze the concepts and theories expounded by some Malaysian literary figures in their efforts to establish solid premise for an ideal Islamic Literary theory. Based on this study, the Islamic literary theory used to be regarded as utopian notion of Islamic Literature has been turned into the acceptable notion nowadays in the Malaysian academic circle. Currently, the discussion has already been related to the forms, contents, roots and philosophies as the foundations of Islamic literature and its theories. Based on a brief yet comprehensive treatment of the subject, this writer finds that mohd Affandi Hasan has managed to make a paradigm shift in discussing Islamic literature in Malaysia after he has founded the vision of New Malay Literature as a new Islamic literary theory. ABSTRAK ABSTRACT